Главные компоненты полей геопотенциала в западном секторе Южного полушария - Галич, Е.А.; Школьный, Е.П.; Севастьянов, А.И. (Видавничий дім "Академперіодика" НАН України, 2008)
The basic features of a statistical structure of the fields of 925, 850, 500 and 200 gPa isobaric surfaces in the Western sector of the South hemisphere are exposed. The main components of these fields have got. A diphasic oscillation characterizing the intercommunication of vortex
components in the western-east transfer between the south aquatoria of the Pacific and Atlantic oceans is established. The features of temporal changeability of the large-scale component of circulation processes in the atmosphere in the second half of the XX century are shown.